Implementation of Okun Law Before Autonomy and After Regional Autonomy 1979-2022 - Nabila, Alfira (Journal of International Conference Proceedings, 2023)
Regional Autonomy is carried out by many countries, including Indonesia. Autonomy is intended to provide better public services. The freedom to take initiative on the basis of granting regional autonomy opens up opportunities for regions to develop their potential to increase economic growth. High economic growth should be able to reduce unemployment. High unemployment rates have an impact on slowing the rate of economic growth. This research uses a paired t-test to see the differences between before and after regional autonomy and the analytical method used is the Vector Error Correction Model (VECM) to analyze the relationship between variables in the long and short term. The results of data analysis show that there is a one-way causal relationship between economic growth and unemployment which is significant and in the short term, the relationship between the unemployment rate variable and economic growth is only found in lag 3. In the long term the unemployment rate variable has a negative relationship with the unemployment rate. It can be concluded that Okun's law only exists in the long term.